2017
DOI: 10.1080/09687599.2017.1331837
|View full text |Cite
|
Sign up to set email alerts
|

Personal sacrifice and corporate cultures: career progression for disabled staff in higher education

Abstract: Disabled people are under-represented in higher education\ud (HE), especially in senior posts. This article reports research\ud on the perspectives of career progression into leadership\ud held by disabled staff in one post-1992 university. Findings\ud indicated that some participants were already engaged in\ud leadership or aspired to such roles, and reported positive\ud experiences. However, participants also experienced barriers\ud to progression, including a lack of awareness of equality\ud and diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…More generally, in the USA and UK at least, the marketisation of higher education (Cribb and Gewirtz 2013; Martin 2016) creates a targetdriven culture where departments rely on their ability to recruit students, to gain high scores on 'student satisfaction', and simultaneously to produce academic papers which are graded by panels of 'experts' in order to reward those institutions where research excellence is demonstrable. In that culture of commodification, it is maybe unsurprising that the experiences of disabled staff within universities have generally been shown by research to be problematic (Brewster et al 2017;Brown and Leigh 2018;Corlett and Williams 2011;Inckle 2018;Waterfield et al 2018;Williams 2011). Despite some positive 'coping strategies' reported, a dominant theme is the normative 'ableism' which is embedded unconsciously in the academy, from recruitment practices (Chan 2005) to physical access (Titchkosky 2008), and the pressure placed on disabled academics (Raymaker 2017).…”
Section: Disability In Higher Educationmentioning
confidence: 99%
“…More generally, in the USA and UK at least, the marketisation of higher education (Cribb and Gewirtz 2013; Martin 2016) creates a targetdriven culture where departments rely on their ability to recruit students, to gain high scores on 'student satisfaction', and simultaneously to produce academic papers which are graded by panels of 'experts' in order to reward those institutions where research excellence is demonstrable. In that culture of commodification, it is maybe unsurprising that the experiences of disabled staff within universities have generally been shown by research to be problematic (Brewster et al 2017;Brown and Leigh 2018;Corlett and Williams 2011;Inckle 2018;Waterfield et al 2018;Williams 2011). Despite some positive 'coping strategies' reported, a dominant theme is the normative 'ableism' which is embedded unconsciously in the academy, from recruitment practices (Chan 2005) to physical access (Titchkosky 2008), and the pressure placed on disabled academics (Raymaker 2017).…”
Section: Disability In Higher Educationmentioning
confidence: 99%
“…The data illustrate the individualist approach of adjustments place considerable burden on disabled employees, who are already managing their workload and impairments. To reiterate, the inclusion of disabled employees in strategic and operational planning groups may also help to facilitate these objectives to move towards inclusive higher education (Brewster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Within organisational studies, scholars have identified that work cultures which personify binary discourses can hinder the career progression of women, particular women with disabilities, who work in organisations dominated by a patriarchal and able-bodied system (Brewster et al, 2017). As a consequence of the discussed barriers to employment participation some women with disabilities sacrifice their careers for fear of having to reestablish their credibility in the job role, risking discrimination, harassment and bullying (Author B, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Gender and disability discrimination are a prevalent problem in the workplace, as White middle-class men continue to dominate the top positions in organisations irrespective of women's growing advancements (Sealy et al, 2016;Atewologun et al, 2016). This is more predominant in professional jobs, for example, in higher education management the level of disabled women present is very low (3%) (Brewster et al, 2017). Specific to disability, there are a number of barriers in place that prevent disabled women from progressing into and/or maintaining leadership positions, ensuring that workers with disabilities are stuck at the bottom of the career ladder (Kaye, 2009).…”
Section: Lack Of Awarenessmentioning
confidence: 99%
See 1 more Smart Citation